2000
DOI: 10.1021/ma991121q
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dielectric and Viscoelastic Relaxation Functions of cis-Polyisoprenes:  Test of Tube Dilation Molecular Picture

Abstract: Within the context of the generalized tube model, the tube representing the entanglement constraint is not necessarily fixed in space but moves with time. This tube motion results in constraint release (CR) as well as dynamic tube dilation (DTD) for the chain trapped in the tube. For monodisperse systems, the DTD molecular picture leads to the normalized relaxation modulus µ(t) ()G(t)/GN) being proportional to square of the surviving fraction of the dilated tube. In contrast, the normalized dielectric relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
152
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(162 citation statements)
references
References 30 publications
(128 reference statements)
7
152
1
2
Order By: Relevance
“…Advances have been more forthcoming for polydisperse mixtures of LPs for three reasons, (i) there is a plethora of well-characterized experimental data [60,[206][207][208][209][210][211][212], (ii) rheological models have been built, tested, refined, and calibrated extensively [213], and (iii) it is possible to use approximate "double reptation-" type models [135,214], in lieu of the full tube model [142], which makes the mathematical model and its numerical solution more expedient.…”
Section: Methods and Progressmentioning
confidence: 99%
“…Advances have been more forthcoming for polydisperse mixtures of LPs for three reasons, (i) there is a plethora of well-characterized experimental data [60,[206][207][208][209][210][211][212], (ii) rheological models have been built, tested, refined, and calibrated extensively [213], and (iii) it is possible to use approximate "double reptation-" type models [135,214], in lieu of the full tube model [142], which makes the mathematical model and its numerical solution more expedient.…”
Section: Methods and Progressmentioning
confidence: 99%
“…In the single idealized case of a chain di using in a ®xed tube, the two functions G…t † and F d …t † are identical, since they both simply measure the fraction of original tube still occupied by chain ·…t † ( [31] and see below section 4.2.2). However, experiments on entangled linear, monodisperse polymers comparing both rheology and dielectric relaxation [180,181] have found that in melts, to a good approximation…”
Section: 7mentioning
confidence: 99%
“…Therefore, a test of the CR feature is desired for polymers other than PS so that the CR model 2,3) can be refined on a rigid experimental basis. This test is desired in particular for cis-polyisoprenes (PI) for which molecular tests [15][16][17][18][19][20][21][22][23][24] of the entanglement dynamics have been recently made with the aid of the combination of the † To whom correspondence should be addressed.…”
Section: 5-7)mentioning
confidence: 99%
“…8, we note that τ obs is longer than τ CR for these systems and the difference between τ obs and τ CR is enhanced time comparable with the reptation time thereby broadening the terminal mode distribution. 2,3) This broadening can be well described through the molecular picture of dynamic tube dilation, [17][18][19][20][21][22][23][24] a coarse-grained picture for the CR mechanism.…”
Section: Cr Contribution To Relaxation In Monodisperse Systemsmentioning
confidence: 99%